2016
DOI: 10.1080/02640414.2016.1227079
|View full text |Cite
|
Sign up to set email alerts
|

Biomechanics, energetics and coordination during extreme swimming intensity: effect of performance level

Abstract: The present study aimed to examine how high- and low-speed swimmers organise biomechanical, energetic and coordinative factors throughout extreme intensity swim. Sixteen swimmers (eight high- and eight low-speed) performed, in free condition, 100-m front crawl at maximal intensity and 25, 50 and 75-m bouts (at same pace as the previous 100-m), and 100-m maximal front crawl on the measuring active drag system (MAD-system). A 3D dual-media optoelectronic system was used to assess speed, stroke frequency, stroke … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
21
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 21 publications
(26 citation statements)
references
References 36 publications
1
21
0
Order By: Relevance
“…21 In parallel with these reductions, Etot increased between 25 and 50 m but then decreased markedly by ~20% in the last 50 m compared with the first 50 m. This change is likely related to the rapid decrease of Ean,al (muscle PCr is depleted in ~10-s) and the fast V O2 kinetics. 16,19 This pattern is consistent with the adaptive dynamics of the metabolic energy chains generally observed during supramaximal exercise of similar duration. 1 Our data showed that O2 increased rapidly and reached its maximal value at 50 m. The O2 kinetics from the first 30-s of exercise (up to 4.2 ± 0.7 l•min -1 ) appeared faster than that observed by Jalab et al 5 in swimmers with a lower performance level who only reached their peak O2 after 75 m. The time constant for O2 kinetics was equal to or less than 10-15-s, consistent…”
Section: Discussionsupporting
confidence: 86%
See 3 more Smart Citations
“…21 In parallel with these reductions, Etot increased between 25 and 50 m but then decreased markedly by ~20% in the last 50 m compared with the first 50 m. This change is likely related to the rapid decrease of Ean,al (muscle PCr is depleted in ~10-s) and the fast V O2 kinetics. 16,19 This pattern is consistent with the adaptive dynamics of the metabolic energy chains generally observed during supramaximal exercise of similar duration. 1 Our data showed that O2 increased rapidly and reached its maximal value at 50 m. The O2 kinetics from the first 30-s of exercise (up to 4.2 ± 0.7 l•min -1 ) appeared faster than that observed by Jalab et al 5 in swimmers with a lower performance level who only reached their peak O2 after 75 m. The time constant for O2 kinetics was equal to or less than 10-15-s, consistent…”
Section: Discussionsupporting
confidence: 86%
“…with the fastest values observed in previous studies. 16,19 The high swimming speed of the faster swimmers in our study induced rapid adjustment of O2, with a near maximal fraction of O2 reached quickly. This time course of O2 increase has also been observed in other sports during all-out testing.…”
Section: Discussionmentioning
confidence: 59%
See 2 more Smart Citations
“…Biomechanical characteristics are important swimming performance determinants, fundamental in understanding propulsion mechanics in the highly specific hydrodynamic environment. Analyzing swimmers' force production should be a priority in their training control and research, as an effective propulsion is fundamental for competitive success [1][2][3]. For this purpose, tethered swimming has been one of the most frequently used methods, yielding substantial associations between tethered forces and swimming performance in sprint events [4][5][6].…”
Section: Introductionmentioning
confidence: 99%